2001
DOI: 10.1080/09540120120043982
|View full text |Cite
|
Sign up to set email alerts
|

The role of family and friend social support in reducing emotional distress among HIV-positive women

Abstract: The purpose of this study was to examine HIV-positive women regarding their perceptions of family and friend social support and mental health outcomes. Regression models were constructed for five mental health outcomes. Results indicated that while each outcome has slightly different significant predictors, perceived family support was predictive of the reduced loneliness over the past few days and past year, stress, and presence of depressive symptoms. Implications for researchers and therapists are discussed. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
64
2
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(79 citation statements)
references
References 17 publications
7
64
2
6
Order By: Relevance
“…There is a well-documented inverse relationship between social support and depression among HIV-infected populations (Kalichman, DiMarco, Austin, Luke, & DiFonzo, 2003;McDowell & Serovich, 2007). Some studies have suggested that perceived social support is more important than actual support (Serovich, Kimberly, Mosack, & Lewis, 2001) and that women rely more on social support compared with men in similar situations (Hurdle, 2001). Social support is also shown to be positively associated with disclosure of HIV-positive status (Kalichman et al, 2003;Smith et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…There is a well-documented inverse relationship between social support and depression among HIV-infected populations (Kalichman, DiMarco, Austin, Luke, & DiFonzo, 2003;McDowell & Serovich, 2007). Some studies have suggested that perceived social support is more important than actual support (Serovich, Kimberly, Mosack, & Lewis, 2001) and that women rely more on social support compared with men in similar situations (Hurdle, 2001). Social support is also shown to be positively associated with disclosure of HIV-positive status (Kalichman et al, 2003;Smith et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have examined the role of perceived social support in improving the lives of HIV-positive individuals (Friedland et al, 1996;Hays et al, 1990Hays et al, , 1992Kelly et al, 1993;Leserman et al, 1992). Most suggest that social support buffers stress-related or stress-inducing crises, such as depression (Hays et al, 1990(Hays et al, , 1992Johnson et al, 2001;Serovich et al, 2001;Silver et al, 2003;Turner et al, 1993), hopelessness (Johnson et al, 2001), physical distress (Leserman et al, 1999), disclosure to sexual partners (Kalichman et al, 2003;Marks et al, 1991) and psychological well being (Hays et al, 1990;Serovich et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Patients from a variety of medical populations, including HIV, frequently endorse "improved relationships" as a positive outcome of their illness experience (Dunbar et al, 1998;Petrie et al, 1999;Siegel & Schrimshaw, 2000;Thornton, 2002;Updegraff et al, 2002). Although a substantial body of research indicates that social support is associated with better psychological adjustment and use of adaptive coping strategies among HIV+ patients (Hall, 1999;Pakenham & Rinaldis, 2001;Serovich, Kimberly, Mosack, & Lewis, 2001), only two studies have examined the relationship between social support and benefit finding. In a small sample of HIV+ women recruited via community outreach, emotionfocused social support was found to be associated with stress-related growth (Siegel, Schrimshaw, & Pretter, 2005).…”
mentioning
confidence: 99%